Impact of CSR on corporate financial performance: Evidence from Finnish industrial sector - Zhu, Rui (My University, 2025)
This study aims to investigate whether there is a link between corporate social responsibility and profitability in Finnish listed companies from the industrial sector. Since sustainability reporting has become a statutory requirement, it is important to analyse how companies' social responsibility affects various aspects of financial performance. The link between CSR and CFP is analysed through four multiple regression models, where composite ESG scores and individual dimensions are used as independent variables along with three control variables. These are tested against two dependent variables: return on total assets (ROA) and return on equity (ROE). The results show that ESG scores have a significant impact on ROA and ROE. The ESG score is statistically significant on ROA at the 5% significance level, while other disaggregated variables show significant links at all significance levels except the governance dimension. Furthermore, it is shown that the ESG rating also has a significant negative impact on ROE at all significance levels.
Keywords: social responsibility; profitability; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance